Different actors for the same play: the impact of the embryologist performing the embryo transfer. Issue 4 (October 2022) - Cirillo, Federico; Spadaro, Daria; Morenghi, Emanuela; Baccini, Michela; Busnelli, Andrea; Ronchetti, Camilla; Albani, Elena; Parini, Valentina; Patrizio, Pasquale; Levi-Setti, Paolo Emanuele
Abstract: Research question: Does the embryologist performing the embryo transfer impact the cycle outcome, in terms of ongoing pregnancy rate (OPR)? Design: This single-centre retrospective study analysed the results, corrected for main confounders, from 28 embryologists and 32 physicians who performed respectively 24, 992 and 24, 669 fresh embryo transfers (either at cleavage or blastocyst stage) during a 20-year period from January 2000 to December 2019, in a university-affiliated tertiary care assisted reproductive technology (ART) centre. Primary outcome was OPR, defined as the number of viable pregnancies that had completed at least 12 weeks of gestation on the total number of embryo transfers performed. The study also assessed whether the embryologist's experience, measured in terms of number of embryo transfers performed prior to the day of the procedure, had an impact on their performance. The secondary aim was to assess which variable, between the embryologist and physician, more significantly impacted OPR. Results: The overall unadjusted OPR was 22.54%. The embryologist performing the embryo transfer was found to significantly affect the OPR ( P < 0.0001), corrected for potential confounders. However, the physician factor made a slightly greater contribution to the model (likelihood ratio 21.86, P < 0.001 versus likelihood ratio 17.20, P < 0.0001). No significant association was found between the experience of the embryologist and OPR ( P = 0.067). Conclusions: These results show how the 'human factor' influences the chances of a positive outcome in the final step of a high-tech procedure and underline the importance of implementing an operator quality performance programme (both for physicians and embryologists) to ensure the maintenance of benchmark results and eventually retrain underperforming operators.